2018
DOI: 10.1111/ejh.13022
|View full text |Cite
|
Sign up to set email alerts
|

Disease and treatment characteristics of polycythemia vera patients in Belgium: Results from a scientific survey

Abstract: Objective The current survey aimed to gather predefined disease parameters and treatment strategies to characterize the polycythemia vera (PV) patient population in Belgium. Methods Cross‐sectional data from PV patients, seen at least once between May 2014 and May 2015 at 10 sites in Belgium, were collected in aggregated form and analyzed descriptively and quantitatively. Results Data from 343 PV patients were collected. Of these, 174 (50.7%) were male and 256 (74.6%) were ≥60 years of age. Ninety‐two (26.8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In a chart review study from Germany, 1476 PV patients were evaluated and 77.1% were found to be over the age of 60 years [ 12 ]. In a cross-sectional survey from Belgium, 343 PV patients were evaluated and 74.6% of them were ≥60 years of age [ 13 ]. Our cohort was relatively younger (median: 58 years), possibly due to the demographic characteristics of Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a chart review study from Germany, 1476 PV patients were evaluated and 77.1% were found to be over the age of 60 years [ 12 ]. In a cross-sectional survey from Belgium, 343 PV patients were evaluated and 74.6% of them were ≥60 years of age [ 13 ]. Our cohort was relatively younger (median: 58 years), possibly due to the demographic characteristics of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between these two studies was attributed to different follow-up periods of patients or different doses of hydroxyurea used in the centers [ 26 ]. In a cross-sectional study from Belgium, 12% of the patients were reported to have hydroxyurea resistance/intolerance [ 13 ]. This rate was found to be 16% in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For PV, various previous real-world studies have been published, [12][13][14][15][16][17][18][19][20][21] but no study from the Netherlands to date. Real-world study populations reflect daily clinical practice better since the patients do not need to meet various inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…As for the physicians, the advantage of real‐world studies is that they reflect the clinical practices of a broader spectrum of physicians as they do not limit the inclusion to academic expert centers. For PV, various previous real‐world studies have been published, but no study from the Netherlands to date. The limitations of real‐world data include the non‐standardized collection of data.…”
Section: Discussionmentioning
confidence: 99%
“…PV patients have an increased risk of disease transformation to acute myeloid leukemia (AML) or to myelofibrosis (MF). In 2006 WHO (World Health Organization) declared this disease a myeloproliferative neoplasm (Devos et al, 2018). Zebrafish jak2a V581F mutant, an ortholog of human JAK2 V617F , has various common features with polycythemia vera observed in human and can offer essential information about production mechanisms of disease.…”
Section: Fish Models For Erythrocyte Diseasesmentioning
confidence: 99%